Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c2cp43532b
|View full text |Cite
|
Sign up to set email alerts
|

A novel three-step method for preparation of a TiB2-promoted LiBH4–MgH2 composite for reversible hydrogen storage

Abstract: The reversible dehydrogenation properties of the 2LiBH(4)-MgH(2) composite can be effectively improved by incorporating heterogeneous nucleation agents, typically transition metal borides. A careful study of the 2LiBH(4)-MgH(2) composite with a titanium trifluoride (TiF(3)) additive finds that using the conventional one-step milling method renders only a partial conversion from TiF(3) to titanium boride (TiB(2)) through an intermediate of titanium hydride (TiH(2)). Based on a fundamental understanding of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…First, it should be pointed out that all of the components have been counted to calculate the hydrogen capacity. It can be seen that the undoped 2LiBH 4 /MgH 2 composite exhibits a poor kinetics and releases only 4.1 wt% hydrogen at 400 °C in 300 min, indicating that the incubation period for the second dehydrogenation step largely surpasses 300 min, which is consistent with the previous reports . Notably, the nano‐TMB impressively improves hydrogen storage properties of 2LiBH 4 /MgH 2 composite.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…First, it should be pointed out that all of the components have been counted to calculate the hydrogen capacity. It can be seen that the undoped 2LiBH 4 /MgH 2 composite exhibits a poor kinetics and releases only 4.1 wt% hydrogen at 400 °C in 300 min, indicating that the incubation period for the second dehydrogenation step largely surpasses 300 min, which is consistent with the previous reports . Notably, the nano‐TMB impressively improves hydrogen storage properties of 2LiBH 4 /MgH 2 composite.…”
supporting
confidence: 90%
“…However, the real kinetics of the undoped Li‐Mg‐B‐H system is sluggish and high temperature is needed to give an acceptable dehydrogenation rate. Thereby, great efforts have been devoted to exploring efficient additives, which can be classified as chlorides, fluorides, and oxides . Undoubtedly, these additives improved the kinetics of RHC systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been already reported that the presence of H2 overpressure suppresses the further formation of volatile species [46][47][48]. Moreover, Kang et al and Karimi et al have found that the interaction between titanium fluorides (TiF3 and TiF4) and Li-RHC promotes the formation of nanosized TiB2 during milling [49,50]. Moreover, the release of H2 during the processing in the planetary mill has already been verified for several other complex The results obtained from the phase composition equilibrium calculation can be seen in Table 1.…”
Section: Reversible Hydrogen Capacitymentioning
confidence: 99%
“…如何 高效、 弥散的将过渡金属硼化物纳米粒子引入复合体 系是当前的研究重点. 本研究组采用三步制备新方 法, 显著提高了过渡金属硼化物的生成效率及其在 两基体相界面处的分散度, 从而大幅提高了体系的 循环放氢动力学及容量稳定性 [56,57] , 见图 2. 浙大 Chen 研究组 [58] 将预先制备的无定形过渡金属硼化物 纳米颗粒球磨引入基体相, 所制备样品也具有优异 的放氢动力学和循环稳定性, 放氢反应活化能降低 约 40 kJ/mol.…”
Section: 构建反应复合体系unclassified